Antibiotic prophylaxis prior to urodynamic study in patients with traumatic spinal cord injury. Is there an indication? - da Silva, Marcello Torres (Int Braz J Urol, 2019)
STUDY DESIGN: Retrospective cohort of patients with traumatic spinal cord injury (SCI) that have been hospitalized for physical-functional rehabilitation purposes. OBJECTIVES: To compare the incidence of urinary tract infection (UTI) after urodynamic study (UDS) in three hospitals that adopted different protocols with regard to the preparation of patients. SETTING: Sarah Network of Rehabilitation Hospitals, Brazil. MATERIALS AND METHODS: Between 2014 and 2015, 661 patients from three units of the same hospital network, one of which does not use antimicrobial prophylaxis independently of urine culture results, were evaluated after having undergone UDS. The results were compared in both univariate and multivariate analyses (logistic regression). RESULTS: The global rate of UTI after UDS was that of 3.18% (IC 95% 2.1-4.8), with no differences between the units. In the univariate analysis the only variable that was associated with UTI after UDS was that of T6 injuries or above (P = 0.029). The logistic regression has confirmed this result, with an adjusted odds ratio of 3.06 (IC 95% 1.01 to 9.26; P = 0.0476). The use of antimicrobial prophylaxis did not alter that risk. CONCLUSIONS: This study has demonstrated that the use of antimicrobials does not prevent UTI after UDS. Patients with T6 traumatic SCI or above have got three times more chance of developing UTI after UDS if compared to those with a T7 injury or below, independently of the use of antimicrobials. Even in these patients the use of antimicrobials would not be justified.